2002
DOI: 10.1016/s1470-0328(02)01506-9
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolisation for the treatment of symptomatic fibroids in 114 women: reduction in size of the fibroids and women's views of the success of the treatment

Abstract: Objective To assess the reduction in size of fibroids following uterine artery embolisation and to analyse women's views of the success of treatment. Design An uncontrolled case series of 114 consecutive women who underwent uterine artery embolisation for the treatment of fibroids over two years. Setting The Diagnostic and Interventional Radiology Department at The Royal Surrey County Hospital, Guildford, UK. Methods Bilateral uterine artery embolisation was performed for the treatment of symptomatic fibroids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 1 publication
(1 reference statement)
1
20
1
1
Order By: Relevance
“…We have previously published a series of procedures, with a median follow up of 16.7 months, demonstrating that in most cases, the uterus shrank by an average of 67%, 6 paralleling the symptomatic improvement seen. We have also shown that fibroid embolisation was effective for subserous, interstitial and submucous fibroids, irrespective of size or number of fibroids present 7 . The major advantage of fibroid embolisation over other procedures is that it has the potential to affect all fibroids at one procedure, compared with myomectomy for cases of multiple fibroids, where it is difficult to remove every fibroid 8 .…”
Section: Introductionmentioning
confidence: 72%
“…We have previously published a series of procedures, with a median follow up of 16.7 months, demonstrating that in most cases, the uterus shrank by an average of 67%, 6 paralleling the symptomatic improvement seen. We have also shown that fibroid embolisation was effective for subserous, interstitial and submucous fibroids, irrespective of size or number of fibroids present 7 . The major advantage of fibroid embolisation over other procedures is that it has the potential to affect all fibroids at one procedure, compared with myomectomy for cases of multiple fibroids, where it is difficult to remove every fibroid 8 .…”
Section: Introductionmentioning
confidence: 72%
“…There are also concerns about the effectiveness of UAE in large uteri exceeding 24 weeks and generally use of UAE as a treatment option in these women is not advised. The diameter of the largest fibroid >8.5 cm has also been found to predict UAE failure, but was not confirmed in other studies 5 . Therefore, the effect of a large uterus on symptomatic outcome was investigated.…”
Section: Introductionmentioning
confidence: 88%
“…With this form of treatment, based on the hypothesis that control of arterial blood flow will control symptoms, dominant myomas are reduced by 39%-70%, and most patients experience relief of their myoma-related symptoms [23]. Interestingly, regrowth of the treated myomas occurred in only 3.5% of the cases treated in this way.…”
Section: Discussionmentioning
confidence: 99%